Education of Brain Gym As An Effort to Improve Farmers' Cognitive Functions: Edukasi Senam Otak Sebagai Upaya Meningkatkan Fungsi Kognitif Petani (JURNAL UNEJ, 2023)
Older people are the most vulnerable group to be affected by the Covid-19 disease. Many factors can improve the cognitive function of the elderly. One of the efforts is by exercising the brain (brain gym). Brain Gym is a series of simple motion exercises and is an alternative therapy that aims to improve the flow of blood and oxygen to the brain and stimulate both sides of the brain to work. This community service aims to improve the cognitive function of farmers through brain gym education and counseling for farmers who are at risk of experiencing health problems in Gucialit, Lumajang Regency. The methods used in the implementation of health promotion activities are lectures and brain gym simulations as an effort to improve the cognitive function of farmers who are at risk of experiencing health problems in Gucialit.